Antibacterial and regenerative action of fibrin rich in platelets and leukocytes (Revista Brasileira Multidisciplinar, 2025)
Introduction: Regenerative medicine involves, among other biostimulating strategies, the use of blood derivatives in order to regulate and accelerate the healing process. Fibrin rich in platelets and leukocytes (L-PRF) is a resultant platelet with 3 by-products: acellular supernatant serum (SAS), clot and exudate. Despite being promising, there are few studies that characterize the real influence of this platelet concentrate on the repair of cutaneous wounds. Objective: To evaluate, within an in vitro investigative approach, through antibacterial analysis and cytokine and growth factor dosage, the immunomodulatory influence of L-PRF. Method: 10 clinically healthy volunteers were selected. Some women practiced physical activity daily and others weekly. To obtain the L-PRF derivatives, a blood sample was collected, with the amount of 4 tubes of 5 mL of blood from each candidate. Results: The evaluation of the potential antibacterial properties of the volunteers, on Staphylococcus aureus and Pseudomonas aeruginosa, showed positive action in 40% of the total L-PRF by-products. There was selectivity and differentiation, in the intrinsic individuality of each volunteer, when comparing the 3 elements of L-PRF in the inhibition of the growth zone. Then came another stage of the present study, the dosage of cytokines and growth factor, respectively: tumor necrosis factor (TNF), interleukin 10 (IL-10) and transforming growth factor b (TGF-β) in SAS and exudate. Conclusion: In view of the determination of the antibacterial effect of the by-products of L-PRF, exudate and clot, promising results are also evident, in relation to the biomodulatory effect evidenced in this last step, when comparing the SAS and exudate.
Keywords: Regenerative medicine; Biomodulation; Fibrin; Healing; Anti-bacterial